Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Whalers, explorers and scientists: historical perspectives on the development of the antarctic whaling industry - Basberg, Bjørn L (Antarctic challenges : historical and current perspectives on Otto Nordenskjöld's Antarctic expedition 1901-1903, 2004)
Keywords: Carl Anton Larsen; Norge; Sørishavet; ekspedisjoner; forskning; historie; hvalfangere; hvalfangst; pelagisk; polarområdene

Interannual controls on Weddell Sea surface water fCO2 during the autumn–winter transition phase - Bellerby, Richard G.J.; Hoppema, Mario; Fahrbach, Eberhard; de Baar, Hein J.W.; Stoll, Michel H.C. (Deep Sea Research Part I: Oceanographic Research Papers, 2004)
The fugacity of carbon dioxide (fCO2) of the surface waters of the Weddell Sea along the prime meridian has been described for the austral autumn in 1996 and 1998. For individual years, fCO2 has a strong linear relationship with sea surface temperature, although the relationships cannot be reconciled to provide an interannually consistent algorithm for remotely sensed assessment of fCO2. However, from the assumption that Weddell Sea surface water has a single end member (upwelled Warm Deep Water) we have determined the relative contributions of heating, ice-melt, and biological activity on fCO2. A breakdown of the controls shows that the measured annual fCO2 distributions can be recreated for both transects by adjusting solely for thermodynamic forcing, and model adjustments for salinity are small except in regions of significant upwelling during 1998. The incorporation of nitrate utilisation into the model results in a general and significant underestimation of fCO2. This runs contrary to the earlier findings of Sabine and Key (Mar. Chem. 60 (1998) 95) in the Southern Ocean although it is consistent with models in the area (Louanchi et al., Deep-Sea Res. I 48 (2001) 1581). A major caveat to these findings is the significant departure of the thermodynamic model and a tightening of the nitrate-adjusted model in 1998 in areas with deeper mixing in the southern Weddell Sea. We propose that there are two reasons for the discrepancies in our model: the source waters are not as homogenous as the model assumes; and there are geographical and seasonal variations of CO2 exchange with the atmosphere and the input of inorganic carbon and nitrate from below the mixed layer resulting in imbalances in the mixed layer concentration ratios.
Keywords: Sørishavet; Weddellhavet; karbon syklus; karbondioksid; marin biologi; marin kjemi; oseanografi

Two new Antarctic stegocephalid (Amphipoda: Stegocephalidae: Stegocephalinae) species, with implications for the phylogeny and classification of the two genera Pseudo and Schellenbergia - Berge, Jørgen; Vader, Wim (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
Descriptions and figures of two new species of the genus Pseudo Berge & Vader, 2001 (Stegocephalidae: Stegocephalinae) are presented, but the two species are not given formal scientific names due to lack of material (both are only known by a single specimen each). However, the two new species have a significant impact on the classification and proposed phylogeny of the subfamily, as the two genera Pseudo Berge & Vader, 2001 and Schellenbergia Berge & Vader, 2001 now have to be considered synonymous. Pseudo is selected as the senior synonym. A discussion of the relationships among the genera of the subfamily Stegocephalinae is provided.
Keywords: Sørishavet; amfipoder; fylogenetikk; taksonomi; zoologi

A survey of amphipod associates of sea urchins, with description of new species in the genera Lepidepecreella (Lysianassoidea: lepidepecreellid group) and Notopoma (Photoidea: Ischyroceridae) from Antarctic cidarids - Berge, Jørgen; Vader, Wim; Lockhart, Susanne (ANDEEP (Antarctic benthic DEEP-sea) biodiversity: colonization history and recent community patterns: a tribute to Howard L. Sanders, 2004)
The known associations between amphipods and echinoids are listed, separated into five different categories depending upon the nature of the associations. The new species Lepidepecreella andeep, found attached around the mouth of the cidarid sea urchin Aporocidaris antarctica, is described, as well as the new species Notopoma cidaridis. The tubes of the latter were found attached to the spines of the cidarid sea urchin Rhynchocidaris triplopora. These cases represent the first associations reported between amphipods and echinoids in the Antarctic. A key to both genera is provided.
Keywords: Sørishavet; Weddellhavet; amfipoder; krepsdyr; pigghuder; sjøpiggsvin; taksonomi; zoologi

Flytende fabrikker – de norske hvalkokeriene - Bernhardt, Pernille Brastad (Fabrikken, 2004)
Keywords: Nordmenn; Sørishavet; arbeidsforhold; historie; hvalfangstindustri; hvalindustri; hvalkokerier; kulturhistorie; pelagisk; sjøfolk

På hvalfangst under sovjetstjernen - Børresen, Dag Ingemar (Arbeiderhistorie, 2004)
Keywords: Nordmenn; Norge; Sørishavet; arbeiderbevegelse; arbeidsforhold; historie; hvalfangst; pelagisk; sjøfolk

The distribution and speciation of iron along 6°E in the Southern Ocean - Croot, Peter L.; Andersson, Karen; Öztürk, Murat; Turner, David R. (The SWEDARP 1997/98 Expedition, 2004)
The distribution and speciation of iron was determined along a transect in the eastern Atlantic sector (6°E) of the Southern Ocean during a collaborative Scandinavian/South African Antarctic cruise conducted in late austral summer (December 1997/January 1998). Elevated concentrations of dissolved iron (>0.4nM) were found at 60°S in the vicinity of the Spring Ice Edge (SIE) in tandem with a phytoplankton bloom, chiefly dominated by Phaeocystis sp. This bloom had developed rapidly after the loss of the seasonal sea ice cover. The iron that fuelled this bloom was mostly likely derived from sea ice melt. In the Winter Ice Edge (WIE), around 55°S, dissolved iron concentrations were low (<0.2nM) and corresponded to lower biological productivity, biomass. In the Antarctic Polar Front, at approximately 50°S, a vertical profile of dissolved iron showed low concentrations (<0.2nM); however, a surface survey showed higher concentrations (1–3nM), and considerable patchiness in this dynamic frontal region. The chemical speciation of iron was dominated by organic complexation throughout the study region. Organic iron-complexing ligands ([L]) ranged from 0.9 to 3.0nM Fe equivalents, with complex stability logKFeL′=21.4–23.5. Estimated concentrations of inorganic iron (Fe′) ranged from 0.03 to 0.79pM, with the highest values found in the Phaeocystis bloom in the SIE. A vertical profile of iron-complexing ligands in the WIE showed a maximum consistent with a biological source for ligand production and near surface minimum possibly consistent with loss via photodecomposition. This work further confirms the role iron that has in the Southern Ocean in limiting primary productivity.
Keywords: Bouvetøya; Sørishavet; biogeokjemi; marin kjemi; oseanografi

Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Evaluating global ocean carbon models: The importance of realistic physics - Doney, Scott C; Lindsay, Keith; Caldeira, Ken; Campin, J.-M.; Drange, Helge; Dutay, Jean-Claude; Follows, Michael; Gao, Yongqi; Gnanadesikan, Anand; Gruber, N; Ishida, Akio; Joos, Fortunat; et al. (Global Biogeochemical Cycles, 2004)
A suite of standard ocean hydrographic and circulation metrics are applied to the equilibrium physical solutions from 13 global carbon models participating in phase 2 of the Ocean Carbon-cycle Model Intercomparison Project (OCMIP-2). Model-data comparisons are presented for sea surface temperature and salinity, seasonal mixed layer depth, meridional heat and freshwater transport, 3-D hydrographic fields, and meridional overturning. Considerable variation exists among the OCMIP-2 simulations, with some of the solutions falling noticeably outside available observational constraints. For some cases, model-model and model-data differences can be related to variations in surface forcing, subgrid-scale parameterizations, and model architecture. These errors in the physical metrics point to significant problems in the underlying model representations of ocean transport and dynamics, problems that directly affect the OCMIP predicted ocean tracer and carbon cycle variables (e.g., air-sea CO2 flux, chlorofluorocarbon and anthropogenic CO2 uptake, and export production). A substantial fraction of the large model-model ranges in OCMIP-2 biogeochemical fields (±25–40%) represents the propagation of known errors in model physics. Therefore the model-model spread likely overstates the uncertainty in our current understanding of the ocean carbon system, particularly for transport-dominated fields such as the historical uptake of anthropogenic CO2. A full error assessment, however, would need to account for additional sources of uncertainty such as more complex biological-chemical-physical interactions, biases arising from poorly resolved or neglected physical processes, and climate change.
Keywords: Sørishavet; biogeokjemi; hydrografi; karbon syklus; karbondioksid; klimaendringer; oseanografi

Den første norske oljealderen - Elstad, Åsa (Norsk polarhistorie, 2004)
Keywords: Sørishavet; ekspedisjoner; hvalfangstindustri; hvalolje; pelagisk

"Havfruer" og sjøkvinner - Elstad, Åsa (Kystkvinner i Norge, 2004)
Keywords: Norge; Sørishavet; Vestfold; hvalfangst; kulturhistorie; pelagisk

Ein grådig fangstnasjon? - Elstad, Åsa; Finstad, Bjørn-Petter (Norsk polarhistorie, 2004)
Keywords: Sørishavet; hvalfangstselskaper; hvalindustri; hvalolje; kulturhistorie; pelagisk; politikk; økonomi

Ice shelf water overflow and bottom water formation in the southern Weddell Sea - Foldvik, Arne; Gammelsrød, Tor; Østerhus, Svein; Fahrbach, Eberhard; Rohardt, Gerd; Schröder, Michael; Nicholls, Keith William; Padman, Laurie; Woodgate, Rebecca A. (Journal of Geophysical Research: Oceans, 2004)
Cold shelf waters flowing out of the Filchner Depression in the southern Weddell Sea make a significant contribution to the production of Weddell Sea Bottom Water (WSBW), a precursor to Antarctic Bottom Water (AABW). We use all available current meter records from the region to calculate the flux of cold water (<−1.9°C) over the sill at the northern end of the Filchner Depression (1.6 ± 0.5 Sv), and to determine its fate. The estimated fluxes and mixing rates imply a rate of WSBW formation (referenced to −0.8°C) of 4.3 ± 1.4 Sv. We identify three pathways for the cold shelf waters to enter the deep Weddell Sea circulation. One path involves flow constrained to follow the shelf break. The other two paths are down the continental slope, resulting from the cold dense water being steered northward by prominent ridges that cross the continental slope near 36°W and 37°W. Mooring data indicate that the deep plumes can retain their core characteristics to depths greater than 2000 m. Probably aided by thermobaricity, the plume water at this depth can flow at a speed approaching 1 m s−1, implying that the flow is occasionally supercritical. We postulate that such supercriticality acts to limit mixing between the plume and its environment. The transition from supercritical to slower, more uniform flow is associated with very efficient mixing, probably as a result of hydraulic jumps.
Keywords: Sørishavet; Weddellhavet; havstrømmer; isshelf; oseanografi

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Effect of solar radiation and the subsequent dark periods on two newly isolated and characterized Antarctic marine bacteria - Hernández, Edgardo A; Ferreyra, Gustavo A; Mac Cormack, Walter P (Polar Research, 2004)
Two strains of psychrotolerant Antarctic marine bacteria were isolated and characterized using biochemical and molecular techniques. Sequencing of 16S rRNA gene showed that UVvi strain belongs to the genus Arthrobacter whereas UVps strain is related to the Flexibacter-Cytophaga-Bacteroides (FCB) group. Response of the strains to solar radiation was studied during the summer of 1999 in Potter Cove, near Jubany station (South Shetland Island, Antarctica). The effect of photosynthetically available radiation (PAR, 400-700 nm), ultraviolet-A (UV-A, 320-400 nm) and ultraviolet-B radiation (UV-B, 280-320 nm) on cell viability was studied using mixed cultures in quartz bottles covered with interferential filters and exposed to solar radiation. In all experiments, four treatments were used: dark (with light screened out), PAR (with UV radiation screened out), PAR+UV-A (UV-B screened out) and PAR+UV-A+UV-B. Under the assayed conditions, PAR+UV-A and PAR+UV-A+UV-B radiation showed similar negative effects on the viability of the studied strains. However, at the end of the exposure time, mortality values in PAR+UV-A+UV-B treatments were higher than those observed under PAR+UV-A treatments. In both PAR+UV-A and PAR+UV-A+UV-B treatments we observed high levels of hydrogen peroxide compared with the dark control. The Arthrobacter UVvi strain showed significant recovery in dark conditions after exposure to the PAR+UV-A but not after the PAR+UV-A+UV-B treatment. This strain proved to be more resistant to UV radiation than the FCB group-related UVps strain. The results showed that UV radiation has a deleterious effect on these Antarctic marine bacteria and also revealed that the analysed components of the Antarctic bacterioplankton may have different responses when they are exposed to the same irradiance conditions.
Keywords: Sørishavet; UV-stråling; bakterier; biokjemi; marin biologi; ozonlaget; plankton; ultrafiolett stråling

Input of Glaciomarine Sediments along the East Antarctic Continental Margin; Depositional Processes on the Cosmonaut Sea Continental Slope and Rise and a Regional Acoustic Stratigraphic Correlation from 40° W to 80° E - Kuvaas, Berit; Kristoffersen, Yngve; Guseva, J.; Leitchenkov, German; Gandjukhin, V; Kudryavtsev, Genadii (Marine Geophysical Researches, 2004)
Multichannel seismic reflection data from the Cosmonaut Sea margin of East Antarctica have been interpreted in terms of depositional processes in the continental slope and rise area. A major sediment lens is present below the upper continental rise along the entire Cosmonaut Sea margin. The lens probably consists of sediments supplied from the shelf and slope, being constantly reworked by westward flowing bottom currents, which redeposited the sediments into a large scale drift deposit prior to the main glaciogenic input along the margin. High-relief semicircular or elongated depositional structures are also found on the upper continental rise stratigraphically above the regional sediment lens, and were deposited by the combined influence of downslope and alongslope sediment transport. On the lower continental rise, large-scale sediment bodies extend perpendicular to the continental margin and were deposited as a result of downslope turbidity transport and westward flowing bottom currents after initiation of glacigenic input to the slope and rise. We compare the seismostratigraphic signatures along the continental margin segments of the adjacent Riiser Larsen Sea, the Weddell Sea and the Prydz Bay/Cooperation Sea, focussing on indications that may be interpreted as a preglacial-glaciomarine transition in the depositional environment. We suggest that earliest glaciogenic input to the continental slope and rise occurred in the Prydz Bay and possibly in the Weddell Sea. At a later stage, an intensification of the oceanic circulation pattern occurred, resulting in the deposition of the regional plastered drift deposit along the Cosmonaut Sea margin, as well as the initiation of large drift deposits in the Cooperation Sea. At an even later stage, possibly in the middle Miocene, glacial advances across the continental shelf were initiated along the Cosmonaut Sea and the Riiser Larsen Sea continental margins.
Keywords: Sørishavet; Weddellhavet; marin geofysikk; marin geologi; oseanografi

Seismic expression of glaciomarine deposits in the eastern Riiser Larsen Sea, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J.; Gandjukhin, V. (Marine Geology, 2004)
By studying multichannel seismic data across the continental slope and rise of the eastern Riiser Larsen Sea and through a comparison with other East Antarctic continental margins, the base of the glaciomarine deposits has been traced in this area. The seismic data reveal the presence of large channel-levee complexes as well as multiple types of contourite accumulations. Downslope and alonglope processes thus interacted in forming the glaciomarine deposits. The deposits are attributed to the advances of ice sheet, delivering huge amounts of sediment to the shelf edge and upper slope during glacial maxima. Oversteepening and instability generated down-slope turbidity currents forming channel–levee complexes whereas the contourite accumulations were probably mostly formed during interglacials. The spatial distribution of the current controlled deposits indicates that bottom currents flow along the western slope of the Gunnerus Ridge.
Keywords: Dronning Maud Land; Sørishavet; marin geologi; oseanografi; seismologi

Southern Ocean climate variability - Nielsen, Simon Harder Holm (University of Tromsø and Norwegian Polar Institute, 2004)
Keywords: Sørishavet; havnivå; holocene; klimaendringer

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Iron enrichment and photoreduction of iron under UV and PAR in the presence of hydroxycarboxylic acid: implications for phytoplankton growth in the Southern Ocean - Öztürk, Murat; Croot, Peter L.; Bertilsson, Stefan; Abrahamsson, Katarina; Karlson, Bengt; David, Roland; Fransson, Agneta; Sakshaug, Egil (The SWEDARP 1997/98 Expedition, 2004)
Iron(III) photoreduction and the responses of phytoplankton under ultraviolet (UV) and photosynthetically available radiation (PAR) were investigated with the presence of hydroxycarboxylic acid (glucaric acid (GA), a model compound for organic acids excreted by phytoplankton). The incubation experiments were carried out on board using seawater samples collected in the location of the winter ice edge (WIE) and the spring ice edge (SIE) of the Southern Ocean. In this paper, we focus on the results of experiment in WIE. Throughout the experiments, dissolved Fe(II), major nutrients and in vivo fluorescence were monitored regularly. In addition, Chl-a, POC/PON, cell densities of phytoplankton and bacteria, bacterial production, organic peroxide, hydrogen peroxide and total CO2 were measured. The results from the WIE show that iron enrichment had a substantial effect on phytoplankton growth rate. Fe(III) addition in the presence of GA (FeGA) gave higher Fe(II) concentration and higher growth rate of phytoplankton than those in controls. Our results suggest that hydroxycarboxylic acid had a significant chemical and biological impact. The presence of GA influenced iron photochemistry and iron availability to phytoplankton. Phytoplankton growth responses to iron enrichments in incubations under UV and PAR were completely dissimilar. It seems that FeGA addition prominently changes the harmful effect of UV on the phytoplankton population. This study provides preliminary information on how the photoreduction of iron(III) and the phytoplankton growth are affected by iron enrichment in the presence of hydroxycarboxylic acid.
Keywords: Sørishavet; biokjemi; fotosyntese; marin biologi; oseanografi; phytoplankton

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

17th International FRISP Workshop held at the British Antarctic Survey, Cambridge, U.K. on 17th and 18th June 2003 - Smedsrud, Lars H. (Forum for Research into Ice Shelf Processes Report, 2004)
Keywords: Antarktis; Sørishavet; glasiologi; havis

Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, Tim; van Leeuwe, Maria A.; Granum, E.; Weissing, Franz J.; Bellerby, Richard G. J.; Gieskes, W. W. C.; de Baar, Hein J. W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April–May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a-specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 μmol photons m−2 s−1, an irradiance comparable with the one at 20–45 m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1–0.6 μg Chl a L−1) was mainly caused by light limitation in the deep wind mixed layer (>40 m). Regional differences in Chl a-specific carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis, whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100 m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis. The glucan respiration rate was almost twice as high during the dark phase as during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.
Keywords: Sørishavet; biokjemi; fotosyntese; fytoplankton; marin biologi; oseanografi; planteplankton

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer